Promoting Neuroprotective Care in Neonatal Intensive Care Units and Preterm Infant Development: Insights From the Neonatal Adequate Care for Quality of Life Study. (14th November 2016) - Montirosso, Rosario; Tronick, Ed; Borgatti, Renato
Abstract: During their stay in a neonatal intensive care unit (NICU), preterm infants are exposed to adverse stressful experiences that deplete their resources and often result in problematic functioning and developmental outcomes. The impact of specific developmental care practices (e.g., kangaroo care) on preterm infants has been researched extensively. Moreover, the dissemination of knowledge about developmental care has facilitated broader neuroprotective care (NC) that combines different kinds of developmental care practices in different NICUs. However, little is known about how variation in NC affects infants and their long‐term developmental outcomes. Using the findings from the Neonatal Adequate Care for Quality of Life project, in this article, we discuss how variation in the NC incorporated by NICUs into standard care affects short‐ and long‐term outcomes in children born preterm.